2005
DOI: 10.1093/carcin/bgi071
|View full text |Cite
|
Sign up to set email alerts
|

LMP7/TAP2 gene polymorphisms and HPV infection in esophageal carcinoma patients from a high incidence area in China

Abstract: Esophageal carcinoma is characterized by a widely ranged incidence variation among the different geographic regions. Anyang is a county in Henan Province of North China with the highest prevalence of esophageal carcinoma. Human papillomavirus (HPV) infection has been linked to the etiology of esophageal cancer in this area. In this study, we investigated correlations of the polymorphisms at low molecular weight polypeptide (LMP) and transporters with antigen processing (TAP) genes, with the risk of esophageal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 32 publications
5
78
4
Order By: Relevance
“…Furthermore, eight studies were excluded because of the limited number. In total, we included 26 eligible studies in the meta-analysis (Cao et al, 2005;Yang et al, 2005;Dai et al, 2007;He et al, 2007;Shuyama et al, 2007;Zhou et al, 2007;Chen et al, 2008;Li et al, 2008;Liu et al, 2008;Lu et al, 2008;Zhao et al, 2009;Liu et al, 2010;Koshiol et al, 2010;Wang et al, 2010;Ayshamgul et al, 2011;Han et al, 2011;Zhang et al, 2011;Guo et al, 2012;Hu et al, 2012;Qu et al, 2012;Liu et al, 2013;Zhang et al, 2013;Cui et al, 2014;Liu et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, eight studies were excluded because of the limited number. In total, we included 26 eligible studies in the meta-analysis (Cao et al, 2005;Yang et al, 2005;Dai et al, 2007;He et al, 2007;Shuyama et al, 2007;Zhou et al, 2007;Chen et al, 2008;Li et al, 2008;Liu et al, 2008;Lu et al, 2008;Zhao et al, 2009;Liu et al, 2010;Koshiol et al, 2010;Wang et al, 2010;Ayshamgul et al, 2011;Han et al, 2011;Zhang et al, 2011;Guo et al, 2012;Hu et al, 2012;Qu et al, 2012;Liu et al, 2013;Zhang et al, 2013;Cui et al, 2014;Liu et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported an association between the genetic variants of Arg to His substitution at codon 60 of Association between LMP2 and LMP7 gene polymorphisms and the risk of gastric cancer: A case-control study LMP2 (LMP2-60) and Gln to Lys substitution at codon 145 of LMP7 (LMP7-145) and the risk of numerous malignant diseases, including ovarian cancer, colon cancer and esophageal carcinoma (13)(14)(15). However, the association between LMP2 and LMP7 polymorphisms and the risk of GC has not been investigated to date.…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphisms of TAP genes have been associated with various diseases such as tuberculosis (Wang et al, 2012), ankylosing spondylitis (Feng et al, 2009), leprosy (Shinde et al, 2013), idiopathic bronchiectasis (Dogru et al, 2007), cystic fibrosis (Ozbas-Gerceker et al, 2002) and also with the risk of occurence of several malignant tumors including colon cancer (Yang et al, 2005), cervical carcinoma (Mehta et al, 2007) and esophageal carcinoma (Cao et al, 2005). To the best of our knowledge there has been no study on the association of TAP gene polymorphisms with hematological malignancies.…”
Section: Association Of Tap1 and Tap2 Gene Polymorphisms With Hematolmentioning
confidence: 99%
“…TAP gene polymorphisms were found to be associated with colon cancer (Yang et al, 2005), cervical carcinoma (Mehta et al, 2007) and esophageal carcinoma (Cao et al, 2005). However, literature rewieving yielded no specific study on the role of TAP polymorphisms in the pathogenesis of hematological malignancies.…”
mentioning
confidence: 99%